2022
DOI: 10.1111/1440-1681.13727
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin modulates the faecal microbiota after myocardial infarction in non‐diabetic mice

Abstract: The gut microbiota seems to be a major modulator of cardiovascular diseases, such as myocardial infarction. Dapagliflozin, a sodium glucose cotransporter 2 inhibitor (SGLT2i), is an antidiabetic agent that was recently utilized in patients with cardiovascular diseases. This study aims to investigate the effects of dapagliflozin on the faecal microbiota of postinfarction non‐diabetic mice. A total of 19 male mice were randomly divided into three groups, where two groups were enduced with myocardial infarction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
3
1
Order By: Relevance
“…Our findings demonstrated dapagliflozin could improve endothelial dysfunction in mice undergoing HF via targeting gut microbiota, thereby contributing to the recovery of myocardial function. It is the difference between our findings and the report by Li et al (2023) . The functional prediction of altered microbiota indicated these microbiotas ameliorated endothelial dysfunction in mice with HF by modulating the biosynthesis and degradation of metabolites.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings demonstrated dapagliflozin could improve endothelial dysfunction in mice undergoing HF via targeting gut microbiota, thereby contributing to the recovery of myocardial function. It is the difference between our findings and the report by Li et al (2023) . The functional prediction of altered microbiota indicated these microbiotas ameliorated endothelial dysfunction in mice with HF by modulating the biosynthesis and degradation of metabolites.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent study by Li et al (2023) showed the role of dapagliflozin in gut microbiota based on a model of LDA ligation. They found dapagliflozin modulated gut microbiota to improve myocardial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, empagliflozin was able to promote a selection of SCFAs-producing bacteria, such as Roseburia, Faecalibacterium, and Eubacterium over potentially harmful bacteria, including Escherichia-Shigella, Bilophila, and Hungatella [147]. In another study, a 28-day treatment with dapagliflozin, another SGLT2i, significantly improved cardiac function in the non-diabetic myocardial infarction mice model and modified the gut microbiota composition, increasing the abundance of beneficial bacteria such as Lactobacillaceae [148]. Muribaculaceae and Lactobacillaceae were the main components of the intestinal microbial community after treatment with dapagliflozin, while Muribaculaceae and Erysipelotrichaceae were the ones associated with myocardial infarction.…”
Section: Drugsmentioning
confidence: 97%
“…This provides direction for the development of new biologics or dietary interventions. Secondely, studies have shown that gut microbiota remodeling through certain interventions, such as Lactobacillus johnsonii, dapagliflozin, and flavonoids, can result in enhanced cardiac function after AMI (253)(254)(255). SCFAs have been found to improve cardiomyocyte function and heart contractility (244,256).…”
Section: Microbiomicsmentioning
confidence: 99%